Approaches through which anticipation informs climate governance in South Asia - Muzammil, Maliha; Muiderman, Karlijn; Vervoort, Joost M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This report presents the RE-IMAGINE research in one of its four regions: South Asia. RE-IMAGINE builds on climate foresight expertise of the Climate Change, Agriculture and Food Security (CCAFS) Program and analyses the role of foresight in climate governance across the globe. Scenarios and many other methods and tools are used today to imagine climate futures and develop strategies for realizing new futures while governing climate change. With the proliferation of these processes in sustainability-related research and planning contexts, scrutiny of their role in steering climate actions in the present becomes increasingly important. How can the benefits and challenges of these processes of anticipation be better understood as governance interventions? At the same time, research into anticipatory climate governance processes in the Global South has remained very limited, while these regions are most vulnerable to climate change. The RE-IMAGINE report therefore examines processes of anticipation in four regions of the Global South. The research question we answer in this report is: ‘through what approaches are diverse processes of anticipation used to govern climate change in diverse South Asian contexts?’. In order to answer this question, we first examine what methods and tools are used to anticipate climate futures and their role in climate policy and decision-making. We then closely examine three case studies to understand their approaches to anticipatory governance. Additionally, we present the results of two regional meetings with stakeholders where we discussed the challenges that exist in each country to practice anticipatory climate governance and the opportunities to strengthen capacities in this field. Finally, we present recommendations for strengthening processes of anticipatory climate governance in the region.